2012
DOI: 10.2478/s11536-012-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and social activities in multiple sclerosis patients

Abstract: AbstractDespite that the prevalence of depression has been thoroughly analyzed in multiple sclerosis (MS) patients and affects approximately 15%–20% of the MS population, attention paid to social activities concomitant with anxiety is still too sporadic. The aim of this study was to find the prevalence of anxiety and social activities aggraded/aggravated with anxiety in the MS population in Lithuania and to analyze how it correlates with socio-demographic factors, clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…None of the studies reported the incidence of anxiety disorders, while 41 reported the prevalence of diagnosed anxiety disorders (13, 31.7%), symptoms of anxiety (26, 63.4%), or both (two) (Supplemental Table 2). 3 , 14 , 16 , 18 , 19 , 24 , 26 , 27 , 30 , 32 , 34 , 37 39 , 43 , 50 , 56 80 Diagnosed anxiety disorders or previously undiagnosed anxiety disorders meeting diagnostic criteria were captured using structured diagnostic interviews, medical records review or self-reported diagnoses. Symptoms of anxiety were captured using validated instruments including the Hospital Anxiety and Depression Scale (HADS), Hamilton Anxiety Rating Scale, State-Trait Anxiety Inventory, and Beck Anxiety Inventory.…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies reported the incidence of anxiety disorders, while 41 reported the prevalence of diagnosed anxiety disorders (13, 31.7%), symptoms of anxiety (26, 63.4%), or both (two) (Supplemental Table 2). 3 , 14 , 16 , 18 , 19 , 24 , 26 , 27 , 30 , 32 , 34 , 37 39 , 43 , 50 , 56 80 Diagnosed anxiety disorders or previously undiagnosed anxiety disorders meeting diagnostic criteria were captured using structured diagnostic interviews, medical records review or self-reported diagnoses. Symptoms of anxiety were captured using validated instruments including the Hospital Anxiety and Depression Scale (HADS), Hamilton Anxiety Rating Scale, State-Trait Anxiety Inventory, and Beck Anxiety Inventory.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed the prevalence of anxiety in 33.7 percent of study participants and also agreed with the previous findings. [39][40][41] Of persons experiencing any pain, 88.2 percent met anxiety criteria and this was a significantly higher number in comparison to those anxiety free (46.3 percent, p < 0.001). The mean value of anxiety (HADS-A) was significantly higher in patients experiencing pain compared to pain-free patients (respectively, 12.1 AE 4.9, vs. 4.1 AE 3.9, p < 0.001).…”
Section: Discussionmentioning
confidence: 93%
“…[38][39][40][41] Beiske et al 40 reported that fatigue and younger age at onset were significantly associated with symptoms of depression, whilst fatigue and pain, lower EDSS score and younger age at onset were associated with symptoms of anxiety. Logistic regression model in our study revealed that anxiety was strongly related with pain.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the lifetime prevalence rates for depression, the reported prevalence rates of an anxiety disorder or anxiety symptoms in MS (general anxiety disorder, social anxiety, agoraphobia, etc.) are more homogeneous, ranging from 20 to 44.5% [32][33][34][35][36]. According to the World Health Organisation (WHO), 8.5% of people in the normal population experience a general anxiety disorder.…”
Section: Anxietymentioning
confidence: 99%